A checklist of the helminth parasites of sympatric rodents from two Mayan villages in Yucatán, México - Panti-May, Jesús Alonso; Digiani, María Celina; Palomo-Arjona, Eduardo Emir; Gurubel-González, Yessica Margely; Navone, Graciela T.; Williams, Carlos Machain-; Hernández-Betancourt, Silvia F.; Robles, María Del Rosario (Zootaxa, 2018)
In this survey, 19 species of helminths including Cestoda (Davaineidae, Hymenolepididae, and Taeniidae), Acanthocephala (Oligacanthorhynchidae), and Nematoda (Trichuridae, Ornithostrongylidae, Heligmonellidae, Oxyuridae, and Gongylonematidae) from Rattus rattus, Mus musculus, Sigmodon toltecus, Heteromys gaumeri, and Peromyscus yucatanicus in two Mayan villages in Yucatán, México, were recorded. Ten species of helminths were collected in both localities. The highest species richness was recorded in R. rattus from Xkalakdzonot (6 taxa). Twelve species are new records for Yucatán and two are registered for the first time in México. This survey constitutes the first checklist of helminth parasites in small rodents in the south-southeast of México.